John F. C. Turner y su visión relacional de la vivienda - Oyón, José Luis (Pontificia Universidad Católica del Perú, 2021)
The article reconstructs the relational conception of housing by John F. C. Turner, a thought about inhabiting where as important as the housing physical object are the relationships that its inhabitants maintain with the environment. This vision, taken in essence from Patrick Geddes, began to be forged in the late 1940s, was taking shape during his stay in Peru between 1957 and 1964 and reached his definitive theoretical expression when he moved to the United States. The article finally reflects on the important role played by the Peruvian and American anthropologists with which he collaborated in Lima, and the figure of Charles Abrams in that Turnerian conception

Este artículo reconstruye la concepción relacional de la vivienda de John F. C. Turner, un pensamiento sobre el habitar donde tan importante como el objeto físico vivienda son las relaciones que sus habitantes mantienen con el entorno. Esa visión, tomada en esencia de Patrick Geddes, comenzó a forjarse a finales de la década de 1940, fue tomando forma durante su estancia en el Perú entre 1957 y 1964, y alcanzó su expresión teórica definitiva cuando Turner se trasladó a los Estados Unidos. El artículo reflexiona finalmente sobre el relevante papel desempeñado por los antropólogos peruanos y norteamericanos con los que Turner colaboró en Lima y la figura de Charles Abrams en dicha concepción turneriana.
Keywords: John F. C. Turner; Self-help housing; Relational thinking; Holism; Patrick Geddes; Anarchist urbanism; Lima barriadas; John F. C. Turner; Vivienda autoconstruida; Pensamiento relacional; Holismo; Lima; Barriadas de Lima; Patrick Geddes; https://purl.org/pe-repo/ocde/ford#6.04.08